THE MOST EFFECTIVE ERROR CORRECTION GAMES IN SECOND LANGUAGE LEARNING - Alimova Madinabonu Islomjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: If your students are bored with correcting, it could be a sign that they get too much correction or they don't see the importance of what they are correcting. This can become more problematic if the teacher introduces a game or asks students to spend a few extra hours correcting (perhaps unnecessary) mistakes. With all classes, but the least motivated, students need not be thrilled to discover that something they've been saying for years isn't true, that something could be misunderstood. That something L1 can't translate directly into English, that an English word seems to have been made up somewhere else, or that no one actually said something their middle school English teacher taught them.